YO‘L QOPLAMALARI VA BETON MATERIALLARIGA TALAB: OSIYO VA BOSHQA MINTAQALAR MISOLIDA - Botirova Nodira Sherali qizi, Ortiqulova Jayxuna Jasur qizi, Jo‘rayev Dilrux Tolibovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article explores the process of developing the optimal concrete composition for road pavements using examples from Asian countries. It highlights the use of high-quality concrete in countries such as China, India, Japan, and South Korea in the development of road infrastructure. The article analyzes how natural conditions, technological advancements, and environmental factors influence the selection of concrete composition. Furthermore, a comparison is made between the concrete production technologies and approaches in Asian and European countries.